The characteristics and emissions of low-pressure densified torrefied elephant dung fuel briquette - Artidtaya Mainkaew; Sommas Kaewluan; Adisak Pattiya; Surachai Narrat Jansri (International Journal of Renewable Energy Development, 2023)
Elephant dung is the camp's undigested fiber waste. For more effective waste management, the conversion of dung to torrefied solid and the formation of solid torrefied into fuel briquettes, as well as their properties, were investigated. The dung was improved through torrefaction at 280ºC for 150 sec in a pilot-scale reactor with a feeding rate of 600 g/h. The torrefied elephant dung had 17 MJ/kg of HHV, a solid yield of 79%, and a fixed carbon content of 20%. A mixture of torrefied dung, binder, and water was compressed at 40 bars to a density of 860 kg/m3, or 12 GJ/m3. Their H/C and O/C atomic ratios were in the range of typical biomass. However, due to their moisture content of over 7%, the HHV of the fuel briquettes was below 17 MJ/kg. Moreover, their thermal efficiency was less than 7% due to durability issues, despite having a great fuel ratio and thermal stability. The combustion of these briquettes resulted in less than 850 ppm of CO. To improve the combustibility of this solid biofuel, it is recommended to develop a production process and a suitable stove specifically for these briquettes.